2013
DOI: 10.1007/s10508-013-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

United States Women and Pornography Through Four Decades: Exposure, Attitudes, Behaviors, Individual Differences

Abstract: Responding to a call for research on pornography and women's sexuality made by Weinberg, Williams, Kleiner, and Irizarry (2010), this study assessed pornography consumption, predictors, and correlates using nationally representative data gathered from U.S. women between 1973 and 2010 (N = 18,225). Women who were younger, less religious, and non-White were more likely to consume pornography. Women who consumed pornography had more positive attitudes toward extramarital sex, adult premarital sex, and teenage sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 41 publications
7
86
1
2
Order By: Relevance
“…In individual analyses on porn consumption, political ideology, income, education, age, and marital status are all important variables (Perry, 2016b(Perry, , 2016cStack et al, 2004;Wright, 2013;Wright et al, 2013 …”
Section: Control Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In individual analyses on porn consumption, political ideology, income, education, age, and marital status are all important variables (Perry, 2016b(Perry, , 2016cStack et al, 2004;Wright, 2013;Wright et al, 2013 …”
Section: Control Variablesmentioning
confidence: 99%
“…Consequently, religious groups, and most prominently conservative Protestants in the American context, strongly discourage any type of pornography, viewing it as a form of fornication that rouses and facilitates sexual desires about persons outside of marriage and encourages solo-masturbation (Driscoll, 2009;Sherkat & Ellison, 1997). It is unsurprising, then, that studies of religion's relationship to porn viewing among American adults consistently find that those who report greater religious commitment (measured in a variety of ways) or who hold theologically conservative identities and beliefs are more likely to report either not viewing pornography at all (Doran & Price, 2014;Grubbs et al, 2015;Maddox, Rhoades, & Markman, 2011;Nelson, Padilla-Walker, & Carroll, 2010;Patterson & Price, 2012;Perry, 2016b;Stack, Wasserman, & Kern., 2004;Wright, 2013;Wright, Bae, & Funk, 2013) or doing so less frequently than others (Baltazar, Helm, McBride, Hopkins, & Stevens, 2010;Bridges & Morokoff, 2011;Carroll, Padilla-Walker, Nelson, Olson, Barry, & Madsen, 2008;Hardy, Steelman, Coyne, & Ridge, 2013;Perry, 2016c;Poulsen, Busby, & Galovan, 2013;Short, Kasper, & Wetterneck, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to online erotica, pornography consumption has been found to be common among both men and women in the U.S. (Shaughnessy, Byers, & Walsh, 2011;Wright, 2013;Wright, Bae, & Funk, 2013). In terms of general pornography viewing, 36% of men and 17% of women reported watching at least one pornographic movie in 2010, and these prevalence statistics have stayed rather stable across four decades (Wright, 2013;Wright et al, 2013).…”
Section: Online Sexual Activitiesmentioning
confidence: 99%
“…In terms of general pornography viewing, 36% of men and 17% of women reported watching at least one pornographic movie in 2010, and these prevalence statistics have stayed rather stable across four decades (Wright, 2013;Wright et al, 2013). Meanwhile, with regard to Internet pornography specifically, Shaughnessy et al (2011) found that 83% of young adult men and 21% of young adult women reported solitary viewing of online sexually-explicit videos or photos during the last month.…”
Section: Online Sexual Activitiesmentioning
confidence: 99%